Difference Analysis Between Canine Adenovirus Types 1 And 2 - Zhu, Yanzhu; Xu, Jinfeng; Lian, Shizhen; Zhang, Rui; Hou, Jinyu; Wang, Minchun; Yan, Xijun (Frontiers in Cellular and Infection Microbiology, 2022)
Canine adenoviruses (CAdVs) include type 1 (CAdV-1, virulent strain) and type 2 (CAdV-2, attenuated strain). In recent years, the incidences of CAdV infections are increasing. However, they are difficult to distinguish when the symptoms are untypical. It is pivotal to find the differences between the two virus types for scientific, epidemiological, and specific treatment. CAdV-1 (virulent strain) and CAdV-2 (attenuated strain) induced canine hepatitis (ICH) and tracheobronchitis (ITB), respectively, but the clinical symptom is not obvious. CAdV-1 and CAdV-2 have the same genome structure, diameter, morphological features, and cytopathic features, but the same character hinder the diagnose time of the serotypes. CAdV-1 and CAdV-2 have a difference in the genome sequence, coding proteins, viral activity, hemagglutination patterns. After infection, pathogenicity and transmission route are different between the two serotypes. Sequence alignment, PCR, Real time-PCR assay are useful methods to distinguish the two serotypes. The attenuated live CAdV-2 vaccine is currently used to protect against CAdV-1, but it also has a risk. The further research should focus on the pathogenicity mechanism and the useful vaccine for the two serotypes of canine adenovirus.